REFLEXÕES SOBRE A VISIBILIDADE DE CRIANÇAS E ADOLESCENTES NO CIBERESPAÇO A PARTIR DE UM CURSO DE FORMAÇÃO DE PROFESSORES EM SERVIÇO - FERREIRA, MARINALVA BORGES (2022)
The current educational context brings significant and evolutionary changes with regard to technologies, updates that automatically influence the educational process. Considering this reality, the school goes through transformations in an attempt to follow the process. In this sense, digital media in training are challenges for educators. There are paradigms to be broken, directing us to questions related to practices, considering that the reality of traditional education does not match the demands of the communication and information society. From the above, the problematization of this study is configured in the question: how do teachers in service who work in elementary school (final grades) use digital technologies in cyberspace? The general objective is to research the use and appropriation of digital technologies in teacher training, particularly on the network visibility of children and adolescents. The specific objectives are: a) to research on teacher training in service and digital media; b) to contextualize the network visibility of children and adolescents; c) to acquire knowledge about sociais networks and virtuais crimes in the school context; d) plan and implement a course for teaching in-service training on children and adolescents and their visibility in cyberspace. The methodology is based on bibliographic and field studies, with qualitative data analysis. The data collection instruments used were: a logbook produced by the researcher; two semi-structured questionnaires (final and initial); appendices 1 and 2. The purpose of implementing this course is to reflect, together with the teachers, on the visibility of children and adolescents in cyberspace. The theoretical contribution is based on the LECET/GEEaDTD dissertative studies and its dissemination since 2016, applying the Communication, Education and Technology triad. The research points out that there is still a long way to go in relation to the continuing formation of teachers, leaving evident gaps in this aspect where, in the future, it is possible to continue. Through data analysis, the present work indicates that it is necessary to improve and implement updated and different training proposals, which lead teachers to reflect on the use of Digital Information and Communication Technologies (TDICs) in the pedagogical practice. The questionnaires analyzed show a lack of knowledge regarding the use of TDICs, being restricted only in theories and discourses without practical and concrete experiences. The participants emphasized that the training contributed to the construction of knowledge and possibilities of adaptations of the pedagogical work with children and adolescents through the use of TDICs.